Osebnostne značilnosti in strategije spoprijemanja s stresom, povezane z zdravjem in izgorelostjo pri vojakih Slovenske vojske - Selič, Polona (Zdravstveno varstvo, 2010)
Problem: The study addresses basic personality traits with soldiers who reportlower bio-psycho-social-wellbeing and burnout and therefore perform poorer working effectiveness and motivation. Perception of one''s health and physical well-being may be used as a measure of one''s health condition and consequently a predictor of higher mortality and greater need for health services. Used diagnostic strategy conceptualizes health as a bio-psycho-social well-being and provides broader insight on interdependence among stress, burnout and organizational climate. Method: Self-rated health questionnaire, Eysenck''s personality scales (EPQ-Revised), Folkman-Lazarus Ways of coping questionnaire and Maslach Burnout inventory were administered. Responses of 390 persons were analyzed. Participants were divided into three groups - healthy (SK1-Z), less healthy (by sick leave criteria, injuries were not included; SK2-B) and persons on missions abroad. Members of the third group meet all health criteria and are exposed to special working conditions, since serving abroad. Data was analyzed by statistical package SPSS (v 17.0, SPSS Inc.): performed were t-test, Mann-Whitney''s test, Kruskal-Wallis'' test, Factor analysis (PC-analysis, Kaiser''s normalization) and correlation coefficients. Results: Interpretation is based upon presumption about veracity of responses; nevertheless the possibility of denial is mentioned. Assuming sincere responses, one distinctive key factor burnout is identified. The highest burnout scores have soldiers serving missions and the lowest healthy group (depersonalization: ?2=21,756; p=0,000; reduced personal accomplishment: ?2=7,088; p=0,029; emotional exhaustion: ?2=6,316; p=0,043). Differences between healthy and less healthy persons are explained by personality traits (such as psychosomatic prone personality, neuroticism and psychoticism). Persons serving missions abroad are cynical, macho and distrustful. Burnout (cynicism, lower personal accomplishment) is a symptom ofdestroyed bio-psycho-social well-being and may develop into absenteeism or quitting the job. Conclusion: A redefinition of selection process for admission in the Slovenian Armed Forces is proposed, to test the basic personality traits and release candidates who exceed values for neuroticism and psychoticism, which could reduce the use of less appropriate coping strategies, depersonalization and emotional fatigue and increase work efficiency. Learning interpersonal skills and using protective strategies (noncompetitive physical activities, hobbies) may reduce the functioning of non-changeable (stable) working conditions and requirements. Necessary emotions-focused coping within macho subculture could be achieved by strengthening group cohesion and quality of relationships, thereby creating social support within the collective.
Keywords: izgorelost; osebnostne lastnosti; prihologija; Slovenian Armed Forces; slovenska vojska; stres; vojaki; zdravje